1970
DOI: 10.3126/hren.v8i2.4422
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury - A Case Profile Study from Eastern Region of Nepal

Abstract: Background: Head injury is a common presentation in emergency rooms .Management often is decided by time of trauma, clinical presentations and availability of facilities. Objective: To outline the general characteristics of head injury patients presenting to emergency. Methods: This is an observational (case series) study done in BPKIHS emergency room over a period of six months. All the acute head trauma cases presenting to the department of emergency, BPKIHS, were evaluated based on the semi closed clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…Our findings were thus keeping with the above mentioned literature. Loss of consciousness and vomiting were the most common clinical presentation in patients with head injury which was similar to the study done by Bhandari et al [8] and Agrawal et al [9].…”
Section: Discussionsupporting
confidence: 88%
“…Our findings were thus keeping with the above mentioned literature. Loss of consciousness and vomiting were the most common clinical presentation in patients with head injury which was similar to the study done by Bhandari et al [8] and Agrawal et al [9].…”
Section: Discussionsupporting
confidence: 88%
“…Findings of our study with regard to gender distribution and age group were on par with findings of Bhandari et al who reported the incidence of men as 82% their study. 6 In the present study, the incidence of RTA was lesser in >50 years age group as reported by other studies. Fall from the height was second most common cause in our study, more common in females than males than RTI.…”
Section: Discussionsupporting
confidence: 82%
“…The advantage of GCS is it comprises a set of very simple and easy to perform physical examinations. Based on GCS scoring system, head injuries are categorised as Mild (with score 13-15), moderate (8)(9)(10)(11)(12)(13) and severe (3)(4)(5)(6)(7)(8). The ability to predict patient outcome after TBI has an important role in clinical practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…Neurosurgery facility was already in function on eastern part of Nepal at Biratnagar and Dharan. 1 egneuro Volume 01, 2019…”
mentioning
confidence: 99%